Staphylococcus cohnii hemolysins - isolation, purification and properties - Rózalska, M; Szewczyk, E M (Folia microbiologica, 2008)
A total 355 of Staphylococcus cohnii isolates from hospital environment, patients (newborns), medical staff and from non-hospital environment were tested for hemolytic activity. Ninety-one % of S. cohnii ssp. cohnii and 74.5 % S. cohnii ssp. urealyticus strains exhibited hemolysis synergistic to S. aureus ATCC 25923 strain. Crude preparations of hemolysins of both bacterial subspecies presented delta-hemolysin, but not alpha- and beta-toxin activity. Highly pure hemolysins were obtained by semipreparative SDS-PAGE or by organic solvent extraction from the freeze-dried crude preparations. Native-PAGE and 2D-PAGE showed their high heterogeneity. Molar masses of single hemolysin units estimated by the Tris-Tricine-SDS-PAGE were calculated as 3.47 kDa for S. cohnii ssp. cohnii and 3.53 kDa for S. cohnii ssp. urealyticus.
Keywords: Polsko; infekce spojené se zdravotní péčí; kůže; isoelektrická fokusace; Hemolysin Proteins; Staphylococcal Infections; hemolyziny; Humans; Electrophoresis, Polyacrylamide Gel; Skin; novorozenec; Cross Infection; Isoelectric Focusing; molekulová hmotnost; stafylokokové infekce; Adult; Molecular Weight; Poland; Staphylococcus; elektroforéza v polyakrylamidovém gelu; dospělí; lidé; Personnel, Hospital; Infant, Newborn; personál nemocniční